STATISTICAL DATA ON DEPRECIATION BASES. - Pierpont, W. K. (The Accounting Review, 1948)
The article presents information on the statistical data on depreciation bases. As a result of the drastic rise in construction costs in the past few years and the expectation of a continuation of a high level of prices, it is not surprising that there is considerable discussion today on the problem of the basis to be used for the depreciation of plant assets. This article is devoted instead to the presentation of a series of data showing in a statistical manner the precise nature of the problem. To limit the problem, only depreciation of building cost is considered. The data included herein are taken from the records of a number of residence halls for men and women students at the University of Michigan. The depreciation expense per student per year varies widely that a noticeable effect on comparative operating results of the several halls will be obtained from accruing depreciation on a cost basis. Especially is this the case when it is remembered that revenue rates, salary and wage rates, and food prices, the three major items in a residence hall operating statement, are essentially the same for all halls.